Pengalaman Pasien Diabetes Melitus Dalam Mempertahankan Gula Darah Secara Mandiri Di Wilayah Kerja Puskesmas Kota - Maria Getrida Simon; Yohana Hepilita; Lusia Henny Mariati; Oliva Suyen Ningsih (PROFESSIONAL HEALTH JOURNAL, 2023)
DM is a health problem that affects productivity and reduces the quality of human resources. Diabetes Mellitus is a chronic metabolic disorder caused by the pancreas not being able to produce enough insulin or the body not being able to use insulin effectively. Insulin is a hormone that regulates the balance of blood sugar levels. To regulate the balance of blood sugar levels, treatment that can be focused on diabetics is by changing lifestyle. The urgency of this research is that this research can help patients choose the right way to maintain blood sugar so as to prevent patients from getting diabetic complications and improve the quality of life of Diabetes Mellitus patients. The purpose of this study was to see how the experience of Diabetes Mellitus patients maintains Blood Sugar. This study uses qualitative research methods. The qualitative research method is research that uses an interpretive and naturalistic approach to the focus of the research. Qualitative research also studies phenomena in their natural state without manipulation, and interprets the meaning of these phenomena from the perspective of the actor. Based on this research, it was found that there were 3 themes, namely self-management, support and motivation and lack of knowledge in self-management. Through this research, it is hoped that health workers will be more active in carrying out health promotion